1994
DOI: 10.1002/hep.1840190115
|View full text |Cite
|
Sign up to set email alerts
|

c-met mRNA overexpression in human hepatocellular carcinoma

Abstract: This study was aimed at assessing the presence of c-met overexpression in human hepatocellular carcinoma and at determining whether this feature is associated with a definite clinical or pathological characteristic. Expression of c-met was determined by Northern-blot hybridization of a specific probe (human met proto-oncogene) in 18 tumoral and nontumoral liver samples obtained in 18 cirrhotic patients with hepatocellular carcinoma submitted to surgical treatment. Eight of the 18 hepatocellular carcinomas exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(49 citation statements)
references
References 25 publications
(21 reference statements)
1
47
0
1
Order By: Relevance
“…More than 70% of IGF-II is bound to IGFBP3, the most abundant circulating binding protein for IGFs (1996), Noguchi et al (1996), Neaud et al (1997), Guirouilh et al (2000Guirouilh et al ( , 2001) MET Upregulated in 20-48% Boix et al (1994), Suzuki et al (1994), Kiss et al (1997), Ueki et al (1997), Tavian et al (2000) TGFa (Jones and Clemmons, 1995). Thus, downregulation of IGFBPs may contribute to elevated IGF bioavailability in tumor tissues.…”
Section: Signaling Pathways and Their Dysregulationmentioning
confidence: 99%
See 2 more Smart Citations
“…More than 70% of IGF-II is bound to IGFBP3, the most abundant circulating binding protein for IGFs (1996), Noguchi et al (1996), Neaud et al (1997), Guirouilh et al (2000Guirouilh et al ( , 2001) MET Upregulated in 20-48% Boix et al (1994), Suzuki et al (1994), Kiss et al (1997), Ueki et al (1997), Tavian et al (2000) TGFa (Jones and Clemmons, 1995). Thus, downregulation of IGFBPs may contribute to elevated IGF bioavailability in tumor tissues.…”
Section: Signaling Pathways and Their Dysregulationmentioning
confidence: 99%
“…MET is detectable in most HCCs (B70%; Table 1; Suzuki et al, 1994;Kiss et al, 1997); however, overexpression of the receptor as compared to peritumorous liver tissue is observed in a lower number of tumor samples (20-48%; Boix et al, 1994;Suzuki et al, 1994;Kiss et al, 1997;Ueki et al, 1997;Tavian et al, 2000). This induction in HCC cells may be attributed to different molecular mechanisms, such as genomic alterations (7q gains in 16.8%; Moinzadeh et al, 2005), tumor hypoxia (Pennacchietti et al, 2003) and growth factor-dependent transcriptional activation of MET (e.g.…”
Section: Transforming Growth Factor B Signaling Axismentioning
confidence: 99%
See 1 more Smart Citation
“…16 sion of HGF and c-met protooncogene product with the Increases in c-met pp expression have been reported in percentage of cyclin A / nuclei were compared, the closhepatocytes of many benign and malignant human liver tisest relationship was between c-met protooncogene prodsues. [17][18][19] Furthermore, in experimental hepatic regeneration, uct and cyclin A. In 11 of 20 HCCs (55%), there was no the overexpression of c-met pp in OCs matches that of HGF correlation between HGF positivity and cyclin A.…”
mentioning
confidence: 99%
“…1 Originally identified in the It has been shown that HCCs overexpress c-met pp in comserum of partially hepatectomized rats, 2 HGF has also been parison with normal liver. [17][18][19] We therefore decided to invesisolated from humans and its gene cloned. [3][4][5] HGF's receptor tigate the expression of HGF and c-met pp in a series of has been characterized as the product of the protooncogene benign and malignant liver lesions that involve mature pac-met, 6 which is overexpressed in solid tumors, such as colonic renchymal cells, malignant hepatocytes, and OCs.…”
mentioning
confidence: 99%